Synthesis and analysis of ZnO and CdSe nanoparticles - Ashtaputre, S. S.; Deshpande, Aparna; Marathe, Sayali; Wankhede, M. E.; Chimanpure, J.; Pasricha, R.; Urban, J.; Haram, Santosh K.; Gosavi, S. W.; Kulkarni, S. K. (Pramana-Journal of Physics, 2005)
Zinc oxide and cadmium selenide particles in the nanometer size regime have been synthesized using chemical routes. The particles were capped using thioglycerol in case of ZnO and 2-mercaptoethanol in case of CdSe to achieve the stability and avoid the coalescence. Zinc oxide nanoparticles were doped with europium to study their optical properties. A variety of techniques like UV-Vis absorption spectroscopy, X-ray diffraction (XRD), photoluminescence (PL), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR) and transmission electron microscopy (TEM) were used to carry out structural and spectroscopic characterizations of the nanoparticles.
1st National Conference on Nanoscience and Technology, Pune, INDIA, MAR 07-08, 2005
Keywords: chemical capping; Doping; Nanoparticles; photoluminescence

Synthesis, characterization and optical properties of silver and gold nanowires embedded in mesoporous MCM-41 - Adhyapak, Parag V.; Karandikar, Prashant R.; Dadge, Jagdish W.; Aiyer, Rohini C.; Chandwadkar, Asha J. (Central European Journal of Chemistry, 2006)
Uniform nanowires of silver and gold inside the channels of MCM-41 were prepared by controlled reduction of their respective metal salts with sodium borohydride (NaBH4). Presence of nanowires of silver and gold in MCM-41 were confirmed by high angle X-ray diffraction (XRD) data (peaks between 2 theta = 30 - 60 degrees) and transmission electron microscopy (TEM) confirmed the diameter of the nanowires. Diameter of nanowires is found to be similar to 2.8 nm which is coincident with channel diameter of MCM-41. Optical properties of these heterostructured materials Ag-MCM-41 and Au-MCM-41 reveals the presence of surface plasmon absorption peaks of silver and gold respectively, and the shift in the absorption bands are associated to agglomeration of clusters inside the channels. Room temperature photoluminescence spectra exhibits interesting optical properties as observed for direct band gap semiconductors. Non-linear optical properties (NLO) corresponding to second harmonic generation (SHG) values were also recorded for self supported films of these heterostructured materials. Enhanced optical non-linearity was found to be arising from a corresponding increase of local field near the surface plasmon resonance. Further enhancement in SHG was found with poling due to an induction of orientation order. (C) Versita Warsaw and Springer-Verlag Berlin Heidelberg. All rights reserved.
Keywords: Ag/Au nanowires; MCM-41; photoluminescence; SHG; TEM

Controlled synthesis of ZnO from nanospheres to micro-rods and its gas sensing studies - Navale, Shalaka C.; Gosavi, S. W.; Mulla, Imtiaz S. (Talanta, 2008)
1D ZnO rods are synthesized using less explored hydrazine method. Here we find, besides being combustible hydrazine can also be used as a structure-directing agent. The ratio of zinc nitrate (ZN) to hydrazine is found to control the morphology of ZnO. At lower concentration of ZN as compared with hydrazine the morphology of ZnO is found to be spherical. As we increase the hydrazine content the morphology changes from spherical (diameter similar to 100 nm) to the elongated structures including shapes like Y, T as well dumbbell (diameter similar to 40 nm and length similar to 150 nm). Interestingly for more than 50% of hydrazine ZnO micro-rods are formed. Such rods are of diameter similar to 120 mn having length of about 1 mu m for ZN to hydrazine ratio of 1:9, isolated as well as bundle of rods are seen in scanning electron microscopy (SEM). The X-ray diffraction (XRD) reveals the phase formation with average particle size of 37 nm as calculated using Scherrer's formula. The high-resolution transmission electron microscopy (HRTEM) is also done to confirm the d-spacing in ZnO. Gas sensing study for these samples shows high efficiency and selectivity towards LPG at all operating temperatures. Photoluminescence (PL) study for these samples is performed at room temperature to find potential application as photoelectric material. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Hydrazine; LPG sensor; Nanostructures; photoluminescence; ZnO

New route for preparation of luminescent mercaptoethanoate capped cadmium selenide quantum dots - Wankhede, Manoj E.; Inamdar, Shaukatali N.; Deshpande, Aparna; Thete, Aniket R.; Pasricha, Renu; Kulkarni, Sulabha K.; Harani, Santosh K. (Bulletin of Materials Science, 2008)
We report a synthesis of cadmium selenide quantum dots (Q-CdSe) by refluxing a mixture of cadmium acetate, selenium powder, sodium sulfite and 2-mercaptoethanol in N,N'-dimethyl formamide (DMF)/water solution. X-ray and electron diffractions suggest the formation of hexagonal phase of size quantized CdSe. Based on TEM analysis, the formation of nanoparticles with an average diameter of 3.5 +/- 0.5 nm is inferred. Their sols in DMF and dimethyl sulphoxide (DMSO) gave characteristic absorption peaks at 300 nm and 327 nm, which is attributed to the formation of high quality, size quantized CdSe particles. Extracted particles from the sol were readily redispersed in DMF and DMSO, which were diluted further with water without losing their optical and colloidal properties. FTIR spectroscopy suggested the formation of 2-mercaptoethanol thiolate on the particle surface, with free -OH groups available for linkage. Sols in DMSO and their solutions in water displayed an intense photoluminescence (PL).
National Review and Coordination Meeting on Nanoscience and Nanotechnology, Hyderabad, INDIA, 2007
Keywords: chalcogenides; Chemical synthesis; photoluminescence; semiconductor quantum dots

Influence of process variables on growth of ZnO nanowires by cathodic electrodeposition on zinc substrate - Sheini, Farid Jamali; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A. (Thin Solid Films, 2009)
Influence of the deposition duration and electrolyte concentration on the structural and morphological features of the ZnO thin films, grown by cathodic electrodeposition on zinc substrate followed by annealing in air at 400 degrees C, have been investigated. The surface morphology of the as-synthesized films shows two distinct features, presence of `2-dimensional nanosheets' on the area near the electrolyte-air interface and `granular' nanostructures, below the interface region. However, upon annealing, the formation of ZnO nanowires, possessing length of several microns and diameter less than 20 nm, on the entire substrate is observed. The X-ray and selected area electron diffraction patterns clearly confirm the polycrystalline nature of the ZnO nanowires. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Annealing; Electrodeposition; Nanowires; photoluminescence; scanning electron microscopy; transmission electron microscopy; Zinc oxide

Ecofriendly synthesis and solar photocatalytic activity of S-doped ZnO - Patil, Ashokrao B.; Patil, Kashinath R.; Pardeshi, Satish K. (Journal of Hazardous Materials, 2010)
The S-doped ZnO was prepared by new ecofriendly method, which involves simple mechanochemical synthesis followed by thermal decomposition of bisthiourea zinc oxalate (BTZO) powders. The BTZO was characterized by FTIR and TG-DTA analysis while S-doped ZnO crystallite was characterized by XRD, XPS, SEM, EDXS, and photoluminescence (PL) spectra. X-ray diffraction data suggest the single phase wurtzite structure for S-doped ZnO and the incorporation of sulfur expand the lattice constants of ZnO. Room temperature PL spectra show more number of oxygen vacancies in S-doped ZnO as compare to that of pure ZnO. Photocatalytic activity of S-doped ZnO was checked by means of solar photocatalytic degradation (PCD) of resorcinol, using a batch photoreactor. The PCD efficiency of S-doped ZnO was found to be 2 times greater than that of pure ZnO. The inherent relationship between PL intensity and photocatalytic activity of S-doped ZnO was discussed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Photocatalysis; photoluminescence; Resorcinol; S-doped ZnO; Sunlight; XPS

One-pot synthesis of oleic acid-capped cadmium chalcogenides (CdE: E = Se, Te) nano-crystals - Khanna, P. K.; Rao, K. Srinivasa; Patil, K. R.; Singh, V. N.; Mehta, B. R. (Journal of Nanoparticle Research, 2010)
Surface-capped CdSe and CdTe nano-crystals (NCs) have been synthesized using cadmium acetate, oleic acid and respective tri-octylphosphine chalcogenide (TOPE; E = Se/Te) in diphenyl ether (DPE). Well-dispersed CdSe particles showed two absorption bands at the region of 431-34 and 458-60 nm in optical absorption study. A band-edge emission resulted at 515 nm with an excitation energy of 400 nm, in its photoluminescence (PL) spectrum. Similarly, UV-visible absorption study of CdTe revealed an absorption band at < 700 nm. The broadened X-ray diffraction (XRD) pattern showed that at higher reaction temperature cubic CdSe but hexagonal CdTe can be obtained with crystallite size of < 10 nm. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) revealed that agglomerated particles are of spherical nature. The inter-planar spacing in CdTe was measured to be 0.406 nm, a characteristic of (100) lattice plane in hexagonal CdTe. X-ray photoelectron spectroscopy (XPS) showed that CdSe NCs have better air stability stable than CdTe. Presence of organic moiety around the semiconductor particles was confirmed by infrared (IR) spectroscopy.
Keywords: Chemical synthesis; photoluminescence; Semiconductors; Surface capping

Biogenic synthesis of silver nanoparticles using nicotiana tobaccum leaf extract and study of their antibacterial effect - Prasad, Kumar Suranjit; Pathak, Darshit; Patel, Ankita; Dalwadi, Palak; Prasad, Ram; Patel, Pradip; Selvaraj, Kaliaperumal (African Journal of Biotechnology, 2011)
A green synthesis of silver nanoparticle was carried out using tobacco leaf extract. Synthesized nanoparticles were characterized using UV-Vis absorption spectroscopy, TEM, EDAX, FT-IR and photoluminescence study, respectively. UV-Vis absorption spectroscopy of prepared silver colloidal solution showed absorption maxima at 418 nm. Excitation maximum and emission maximum obtained from photoluminescence study were found at 414 and 576 nm, respectively. TEM analysis showed average particle size of 8 nm, while SAED pattern confirmed the crystalline nature of synthesized nanoparticles. FT-IR analysis indicated the involvement of carboxyl (-C = O), hydroxyl (-OH) and amine (-NH) functional groups of tobacco leaf extract in preparation of silver nanoparticles. EDAX analysis showed proportion of silver (54.55%) among other elements in nanoparticle. Pseudomonas aeruginosa and Escherichia coli DH5 alpha showed highest sensitivity towards silver nanoparticles.
Keywords: FT-IR spectroscopy; photoluminescence; silver nanoparticles; Tobacco; UV-Vis absorption

Electrochemical preparation of luminescent graphene quantum dots from multiwalled carbon nanotubes - Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Chemistry-A European Journal, 2012)
Green luminescent, graphene quantum dots (GQDs) with a uniform size of 3, 5, and 8.2(+/- 0.3) nm in diameter were prepared electrochemically from MWCNTs in propylene carbonate by using LiClO4 at 90?degrees C, whereas similar particles of 23(+/- 2) nm were obtained at 30?degrees C under identical conditions. Both these sets of GQDs displayed a remarkable quantum efficiency of 6.3 and 5.1?%, respectively. This method offers a novel strategy to synthesise size-tunable GQDs as evidenced by multiple characterisation techniques like transmission and scanning electron microscopy, atomic force microscopy, Raman spectroscopy and X-ray diffraction (XRD). Photoluminescence of these GQDs can be tailored by size variation through a systematic change in key process parameters, like diameter of carbon nanotube, electric field, concentration of supporting electrolyte and temperature. GQDs are promising candidates for a variety of applications, such as biomarkers, nanoelectronic devices and chemosensors due to their unique features, like high photostability, biocompatibility, nontoxicity and tunable solubility in water.
Keywords: electrochemical synthesis; graphene; Nanostructures; photoluminescence; quantum dots

Synthesis, spectroscopy, and electrochemical investigation of new conjugated polymers containing thiophene and 1,3,4-thiadiazole in the main chain - Patil, Prashant S.; Haram, Nanda S.; Pal, Ravindra R.; Periasamy, N.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2012)
Novel photoluminescent donoracceptor poly(p-phenylenevinylene)-type conjugated polymers containing thiophene and 1,3,4-thiadiazole units in the main chain were synthesized from 2,5-bis(5-bromomethyl-2-thienyl)-1,3,4-thiadiazole and 1,3/1,4-benzenedialdehyde by WittigHorner reaction. The synthesized polymers were characterized by the use of thermal analysis and spectroscopic (infrared, UV-visible absorption, and photoluminescence) measurement. The resultant material exhibited bluish green, green, and orange fluorescence in their solution and thin film and solid forms, respectively. The redox property of the polymers has also been studied by cyclic voltammetry. The optical and electrochemical studies reveal that these novel polymers are new promising materials for the development of efficient polymer light-emitting diodes. (c) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: conjugated polymers; photoluminescence; thiophene and thiadiazole-containing polymer

Water electrolysis with a conducting carbon cloth: subthreshold hydrogen generation and superthreshold carbon quantum dot formation - Biswal, Mandakini; Deshpande, Aparna; Kelkar, Sarika; Ogale, Satishchandra (ChemSusChem, 2014)
A conducting carbon cloth, which has an interesting turbostratic microstructure and functional groups that are distinctly different from other ordered forms of carbon, such as graphite, graphene, and carbon nanotubes, was synthesized by a simple one-step pyrolysis of cellulose fabric. This turbostratic disorder and surface chemical functionalities had interesting consequences for water splitting and hydrogen generation when such a cloth was used as an electrode in the alkaline electrolysis process. Importantly, this work also gives a new twist to carbon-assisted electrolysis. During electrolysis, the active sites in the carbon cloth allow slow oxidation of its surface to transform the surface groups from COH to COOH and so forth at a voltage as low as 0.2V in a two-electrode system, along with platinum as the cathode, instead of 1.23V (plus overpotential), which is required for platinum, steel, or even graphite anodes. The quantity of subthreshold hydrogen evolved was 24mLcm(-2)h(-1) at 1V. Interestingly, at a superthreshold potential (>1.23V+overpotential), another remarkable phenomenon was found. At such voltages, along with the high rate and quantity of hydrogen evolution, rapid exfoliation of the tiny nanoscale (5-7nm) units of carbon quantum dots (CQDs) are found in copious amounts due to an enhanced oxidation rate. These CQDs show bright-blue fluorescence under UV light.
Keywords: Carbon; electrolysis; Hydrogen; photoluminescence; quantum dots

Band alignment and charge transfer pathway in three phase anatase-rutile-brookite TiO2 nanotubes: an efficient photocatalyst for water splitting - Preethi, L. K.; Mathews, Tom; Nand, Mangla; Jha, S. N.; Chinnakonda, Gopinath S.; Dash, Sitaram (Applied Catalysis B-Environmental, 2017)
The study reports electrochemical synthesis, phase evolution and hydrogen generation efficiency of anatase, anatase-rutile and anatase-rutile-brookite (ARB) TiO2 nanotubes for the first time. The SEM and TEM micrographs confirm the tubular morphology of the samples. The presence of anatase, rutile and brookite phases in a single nanotube is confirmed from high resolution TEM analysis. The water splitting efficiency of the three systems are studied under one sun illumination. It is observed that the anatase-rutile-brookite TiO2 nanotubes are highly efficient compared to anatase-rutile or anatase TiO2 nanotubes. The hydrogen generated by ARB composites, after four hours of one sun illumination, is found to be nearly twice that of anatase TiO2 nanotubes and 1.6 times that of anatase-rutile TiO2 nanotubes. The results suggest that the ARB in single nanotube having two junction interfaces, highly facilitate interparticle charge transfer compared to single junction anatase-rutile or bare anatase TiO2 nanotubes. From the deconvolution of PL spectra and the synchrotron radiation assisted valence band edge analysis, the band diagram for the anatase-rutile-brookite phase is constructed. The charge separation and its transfer pathway for efficient photo-assisted water splitting are delineated. This opens a new route for the simple synthesis and study of tri-phase TiO2 for efficient photocatalytic water splitting compared to the widely studied two phase TiO2. (C) 2017 Published by Elsevier B.V.
Keywords: Anatase-Rutile-Brookite; Hydrogen generation; nanotubes; Photocatalysis; photoluminescence; Valence band edge

Five concomitant polymorphs of a green fluorescent protein chromophore (GFPc) analogue: understanding variations in photoluminescence with pi-stacking interactions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Nikam, Shrikant B.; Puthuvakkal, Anisha; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Acta Crystallographica Section B-Structural Science Crystal Engineering and Materials, 2020)
The synthetically modified green fluorescent protein chromophore analogue 3,4,5-trimethoxybenzylidene imidazolinone (1) yielded five polymorphs (I, II, III, IV, V) concomitantly irrespective of the solvent used for crystallization. The pentamorphic modification of 1 is solely due to the interplay of iso-energetic weak intermolecular interactions in molecular associations as well as the conformational flexibility offered by a C-C single bond, which connects the electron-deficient moiety imidazolinone with the electron-rich trimethoxybenzylidene group. A common structural feature observed in all the polymorphs is the formation of a `zero-dimensional' centrosymmetric dimeric unit through a short and linear C-H center dot center dot center dot O hydrogen bond engaging phenyl C-H and imidazolinone carbonyl oxygen. However, the networking of these dimeric units showed a subtle difference in all the polymorphs. The 2D isostructurality was observed between polymorphs I, II and III, while the other two polymorphs IV and V revealed only `zero-dimensional' isostructurality. The different fluorescence emissions of Form I (blue) and Forms II to V (yellow) were attributed to the differences in pi-stacking interactions. It shows that one can modulate the photophysical properties of these smart materials by slightly altering their crystal structure. Such an approach will aid in developing new multi-colour organic fluorescent materials of varying crystal structures for live-cell imaging and fluorescent sensing applications.
Keywords: green fluorescent protein; hydrogen bonds; isostructurality; photoluminescence; pi-stacking; Polymorphs